2018
DOI: 10.1002/joa3.12086
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of appropriate ICD therapy in Japanese patients with structural heart diseases: A major role of prior sustained ventricular tachycardia in secondary prevention

Abstract: BackgroundImplantable cardioverter defibrillator (ICD) and cardiac resynchronization with a defibrillator (CRT‐D) are established therapies for secondary prevention of sudden cardiac death (SCD) in patients with structural heart disease (SHD), but the rates of subsequent ICD/CRT‐D therapy widely differ among patients with SHD. The aim of this study was to determine clinical factors associated with appropriate therapy for preventing SCD in patients with SHD.MethodsWe enrolled 147 patients with SHD (mean age, 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A previous episode of sustained VT correlates with high rate of appropriate shocks 433–436 . A higher risk of appropriate therapy was seen in a secondary prevention ICD group when compared with a primary prevention ICD group at 5‐year follow‐up, while the rate of inappropriate therapy was comparable 437 .…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Venmentioning
confidence: 99%
“…A previous episode of sustained VT correlates with high rate of appropriate shocks 433–436 . A higher risk of appropriate therapy was seen in a secondary prevention ICD group when compared with a primary prevention ICD group at 5‐year follow‐up, while the rate of inappropriate therapy was comparable 437 .…”
Section: How To Assess Risk For Adverse Outcomes In Patients With Venmentioning
confidence: 99%
“…A previous episode of sustained VT correlates with high rate of appropriate shocks. [441][442][443][444] A higher risk of appropriate therapy was seen in a secondary prevention ICD group when compared with a primary prevention ICD group at 5-year follow-up, while the rate of inappropriate therapy was comparable. 445 Several studies have shown male sex as an independent risk factor for appropriate ICD therapies.…”
Section: Appropriate Shock Predictorsmentioning
confidence: 99%